Plate IX: Uric Acid Crystals (Atlas of Urinary Sediments, 1899)
Plate IX depicting tissue samples and uric acid crystals in various forms. The figures are identified as follows: Figure 1: Shred Of Tissue (part of a tumour) passed with the urine, consisting of closely packed cells (mostly epithelial) covered with acicular crystals and a few rhombic plates of haematoidin. Figure 2: Naked eye appearances of some urinary sediments. Figure 3: Uric Acid Crystals, including whet-stone, spindle, barrel, rectangular, and quadratic forms...[illustrating irregular modes of growth and pigmentation]. Figure 4: Uric Acid Crystals in the form of regular and irregular whet-stone crystals grouped in various ways. Figure 5: Uric Acid Crystals in rosettes and sunflower forms. Figure 6: Uric Acid Crystals in "drusy forms."
Keywords: Urine--Analysis; Crystals; Uric acid; Urology; Scientific illustration